If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 7 = 49 Reorder the terms: 7 + 3x = 49 Solving 7 + 3x = 49 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3x = 49 + -7 Combine like terms: 7 + -7 = 0 0 + 3x = 49 + -7 3x = 49 + -7 Combine like terms: 49 + -7 = 42 3x = 42 Divide each side by '3'. x = 14 Simplifying x = 14
| (8t^2-t-5)(4t^2+8t-1)= | | x^2-13y^2=101 | | 130=14a-10 | | 1.3-5=5.4 | | 16a+10=90 | | -3x-4=-22 | | 5x-10=50-x | | 5(x-2)-8x=-24 | | 0.5s=10 | | (4x-5)(x^2-3x+3)= | | 6x^2-16x+5=0 | | (3x-5)(x^2-2x+6)= | | 4x-1=20-30 | | v^2-v-42= | | absolute(x^2-1)=0 | | 4x-1=2-30 | | 3(u-8)-8u=6 | | 6x-10=100+2x | | k+7=-16 | | 2(3n+2)+2(n+4)=36 | | 126=63n | | 3+3=72 | | 6(x-3)=72/12 | | 3(5x-2)-5(3x-1)=0 | | -9n+12=-5n-12 | | X^2+7x=8x^2 | | -2y-8=3y+7 | | 4-4=14x+4x | | 10x+8-9x=13 | | y(3x+5)=2x-3 | | -2x-2x=33-5 | | b=4c |